Research on Gender Concerns in School Education: A Trend Report - Yadav, Mona; Anand, Mily Roy; Chatterjee, Anannya (INDIAN EDUCATIONAL REVIEW, 2022)
A systematic review of the research studies in the field of Gender Concerns in School Education was taken up with the objective of identifying broad themes and trends of educational researches during the period of 2001–2020. The review helped in identifying gaps in research and through critical discussion on such gaps, prompted new research projects to be conducted. The themes that came up frequently in the research analysed for this report are: Gender and Accessibility, Marginalisation, Gender and Marginalisation in Education, Gender and Curriculum, Gender and Socialisation in Schools and Policy making and their Implementation for Women Education. Each theme was further divided into sub-themes that demonstrated the diversity of researches done to understand gender and education. The report suggests the existing gaps in educational research done on gender and areas of research that can be undertaken in future by researchers working on gender and education